The nuclear transport factor CSE1 drives macronuclear volume increase and macronuclear node coalescence in Stentor coeruleus - Rebecca M. McGillivary; Pranidhi Sood; Katherine Hammar; Wallace F. Marshall (iScience, 2023)
Summary: Stentor coeruleus provides a unique opportunity to study how cells regulate nuclear shape because its macronucleus undergoes a rapid, dramatic, and developmentally regulated shape change. We found that the volume of the macronucleus increases during coalescence, suggesting an inflation-based mechanism. When the nuclear transport factor, CSE1, is knocked down by RNAi, the shape and volume changes of the macronucleus are attenuated, and nuclear morphology is altered. CSE1 protein undergoes a dynamic relocalization correlated with nuclear shape changes, being mainly cytoplasmic prior to nuclear coalescence, and accumulating inside the macronucleus during coalescence. At the end of regeneration, CSE1 protein levels are reduced as the macronucleus returns to its pre-coalescence volume. We propose a model in which nuclear transport via CSE1 is required to increase the volume of the macronucleus, thereby decreasing the surface-to-volume ratio and driving coalescence of the nodes into a single mass.